Sagittal body alignment in a sitting position in children is not affected by the generalized joint hypermobility - Dariusz Czaprowski (Nature Portfolio, 2021)
Abstract Back pain may be related to an improper sitting position. The aim of the study was to assess the sagittal curvatures of the spine in a sitting position in children with generalized joint hypermobility (GJH). The study included 302 children aged 8–14 years. The sagittal curvatures of the spine (sacral slope, lumbar lordosis, thoracic kyphosis with its lower and upper part) were assessed using the Saunders digital inclinometer. In order to assess GJH a 9-point Beighton scale was used. The study revealed no significant differences (p > 0.05) in sagittal curvatures of the spine in a relaxed sitting position between children with and without GJH. Regardless of the occurrence of GJH, kyphotic alignment of the spine was noted in a relaxed sitting. GJH does not affect the position of the trunk in a sagittal plane in a relaxed sitting position in children aged 8–14 years. A relaxed sitting position in children with and without GJH is characterized by a kyphotic position of the spine caused by an improper position of pelvis and lumbar segment of the spine.